2023
DOI: 10.1002/bco2.293
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Proclarix in the diagnostic work‐up of prostate cancer

Basil Kaufmann,
Sharon Fischer,
Alcibiade Athanasiou
et al.

Abstract: ObjectivesThe use of multiparametric magnetic resonance imaging (mpMRI) has been widely adopted in the diagnostic work‐up for suspicious prostate cancer (PCa) and is recommended in most current guidelines. However, mpMRI lesions are often indeterminate and/or turn out to be false‐positive on prostate biopsy. The aim of this work was to evaluate Proclarix, a biomarker test for the detection of relevant PCa, regarding its diagnostic value in all men before biopsy and in men with indeterminate lesions on mpMRI (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A further study compared Proclarix, PSA density, and the MRI-ERSPC risk calculator to select patients for prostate biopsy after multiparametric magnetic resonance imaging (mpMRI). The study concluded that the MRI-ERSPC risk calculator outperformed PSA density and Proclarix in the overall population; however, Proclarix outperformed in a subset of patients within the Prostate Imaging-Reporting and Data System (PI-RADS) ≤ 3 category [471,472]. Several further studies analyzed the combination of Proclarix with the prostate health index [473,474] and MRI [475] and confirmed its utility.…”
Section: Ecm-and Iacs-related Genes and Proteins Taking A Part In Pro...mentioning
confidence: 96%
“…A further study compared Proclarix, PSA density, and the MRI-ERSPC risk calculator to select patients for prostate biopsy after multiparametric magnetic resonance imaging (mpMRI). The study concluded that the MRI-ERSPC risk calculator outperformed PSA density and Proclarix in the overall population; however, Proclarix outperformed in a subset of patients within the Prostate Imaging-Reporting and Data System (PI-RADS) ≤ 3 category [471,472]. Several further studies analyzed the combination of Proclarix with the prostate health index [473,474] and MRI [475] and confirmed its utility.…”
Section: Ecm-and Iacs-related Genes and Proteins Taking A Part In Pro...mentioning
confidence: 96%